Making the Amazon a frontier: where less space is more. Issue 1 (2nd January 2023) - Ioris, Antonio A. R.
ABSTRACT: Frontier-making has always been fundamental for the circulation and accumulation of capital. The perennity of frontier-making is not only due to the demand for minerals, land or other resources, or because frontiers represent fresh market opportunities, but crucially because it operates as compensation for the saturation of the existing capitalist relations in core areas. At the frontier, the conventional sequence of time and space is suspended and reconfigured, allowing room for the decompression of tensions and contradictions. Consequently, spatial frontiers function as a mirror, where the most explicit features of capitalism are vividly exposed. This article examines the meaning and immanence of spatial frontiers, considering them as a laboratory of historical and geographical agency. It entails a reflection upon the necessity, the configuration and the contestation of spatial frontiers, paying particular attention to the economic and territorial incorporation of the Amazon region and the prospects of political resistance.